The Role of Parents in Early Childhood Emotional Development Strategies - Setiowati, Arum; Nuryanto, Iis Lathifah; Kurniawan, Drajat Edy (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The role of parents is crucial in the emotional development of early childhood, which is an important foundation for their social and psychological development in the future. This article aims to explore strategies for developing children's emotions that can be applied by parents in the family environment. This community service activity was carried out through a series of training and mentoring for parents, which included an understanding of children's emotional development, effective communication techniques, and the application of positive emotional stimulation methods. Data were obtained through observation, interviews, and evaluation of parent participation during the program. The results of the community service showed that active involvement of parents in strategies such as giving appreciation, validating emotions, and establishing positive routines can improve children's emotional stability. In addition, a collaborative approach between parents and facilitators also encouraged the creation of a supportive environment for early childhood. Thus, the role of parents in the development of children's emotions not only affects family relationships but is also a key factor in shaping children's emotionally healthy characters.Keywords: Role of parents, emotional development, early childhood, parenting strategies, family training.